Error analysis for the finite element approximation of a radiative transfer model - Führer, Christian; Rannacher, Rolf (RAIRO. Modélisation mathématique et analyse numérique, 1996)
ESAIM: Mathematical Modelling and Numerical Analysis, an international journal on applied mathematics
Elektronische Reproduktion der Druck-Ausgabe 31. Januar 2017
Gesehen am 16.05.2023